Nodes in the city green system, as a urban integration potential - Zinowiec-Cieplik, Kinga (Budownictwo i Architektura / Civil and Architectural Engineering, 2018)
Urban greenery system a significant part of urbanized landscape, may be understood as "areas with specific characteristics identified and designated using the principles of ecology and landscape ecology, the main aim of which is to regulate the ways the natural city environment functions" ( Szulczewska B., Kaliszuk E. 2005 [1]). Greenery system assumes the leading role in building a sustainable and resilient urban environment. The green system structure, according to the generally accepted theory of urban composition (Lynch K. 1960 [5], Wejchert K. 194 [9].) is crystallized by the nodal elements, which ,in this context, are vital,due to "climatic, hydrological and/or biological significance" (Szulczewska B., Kaliszuk E.2005 [1]). While considering city composition together with its landscape as a complex of many layers, such as communication, development, infrastructure and greenery, is it necessary to to emphasize the important role of their mutual penetration, which complements the essence of the functioning of thisvery dynamic and variable city organism. Changes in one of the layers cause distortion in the others. Therefore, the relationships that binds the layers are crucialand their accumulation and dynamics will determine whether the nodal point will eventually be developped. The greenery structure is too fragile with regard to the brutality of communication systems and buildings. However, in the light of the contemporary needs to build a healthy, friendly living environment opened to the change in creative design (Prominski M.2005 [26]), (Prominski M.2005 [26]), the natural system shows potential towards the integration of urban space.